Overhead tank is the potential breeding habitat of Anopheles stephensi in an urban transmission setting of Chennai, India. (December 2016) - Thomas, Shalu; Ravishankaran, Sangamithra; Justin, Johnson; Asokan, Aswin; Mathai, Manu; Valecha, Neena; Thomas, Matthew; Eapen, Alex
Abstract Background Wells and overhead tanks (OHT) are the major breeding sources of the local malaria vector, Anopheles stephensi in the Indian city of Chennai; they play a significant role in vector breeding, and transmission of urban malaria. Many other man-made breeding habitats, such as cemented cisterns/containers, barrels or drums, sumps or underground tanks, and plastic pots/containers are maintained to supplement water needs, temporarily resulting in enhanced mosquito/vector breeding. Correlating breeding habitats with immature vector abundance is important in effective planning to strengthen operational execution of vector control measures. Methods A year-long, weekly study was conducted in Chennai to inspect available clear/clean water mosquito breeding habitats. Different breeding features, such as instar-wise, immature density and co-inhabitation with other mosquito species, were analysed. The characteristics of breeding habitats, i.e., type of habitat, water temperature and presence of aquatic organisms, organic matter and green algal remnants on the water surface at the time of inspection, were also studied. Immature density of vector was correlated with presence of other mosquito species, malaria prevalence, habitat characteristics and monthly/seasonal fluctuations. All the data collected from field observations were analysed using standard statistical tools. Results When the immature density of breeding habitats was analysed, using one-way ANOVA, it was observed that the density did not change in a significant way either across seasons or months. OHTs contributed significantly to the immature population when compared to wells and other breeding habitats of the study site. The habitat positivity of wells and OHTs was significantly associated with the presence of aquatic organisms, organic matter and algal remnants. Significant correlations of malaria prevalence with monthly immature density, as well as number of breeding habitats with immature vector mosquitoes, were also observed. Conclusions The findings that OHTs showed fairly high and consistent immature density ofAn. stephensi irrespective of seasons indicates the potentiality of the breeding habitat in contributing to vector density. The correlation between vector breeding habitats, immature density and malaria prevalence indicates the proximity of these habitats to malaria cases, proving its role in vector abundance and local malaria transmission. The preference ofAn. stephensi to breed in OHTs calls for intensified, appropriate and sustained intervention measures to curtail vector breeding and propagation to shrink malaria to pre-elimination level and beyond.